Jogo de aposta: um assunto de sáude pública ainda negligenciado e em franca expansão no Brasil e no mundo - Elizabeth, Carneiro [UNIFESP] (2024)
Art.1 -The goal of this study was to investigate gambling-related behavior, onset and progression in a sample of at-risk gamblers from th ecommunity. A nationa lhousehold survey was conducted in Brazil, covering individuals 14 years old or older. Subjects were screened for at-risk gambling, those testing positive answered a questionnaire about gambling progression, preferred games and DSM-IV pathological gambling criteria. Out of 3007respondents, 118 were considered at-risk gamblers according to theLie/ Bet Questionnaire.According to the DSM-IV, 32.7% and 24.9% of those were considered problem and pathological gamblers, respectively. Early at-risk gamblers (onset prior to20 years of age), were more likely to be male, to prefer non-commercially structured games, and to chase losses while gambling. Young pathological gamblers (under 35years of age) progressed faster from regular to problem gambling (roughly 2 years) than mature pathological gamblers(12years). Such findings had not been described before because previous reports focused mostly on clinical samples that lack young, male, early-onset gamblers. Gambling programs have not satisfactorily covered this segment of gamblers. Outreach strategies and early interventions should be provided to prevent these individuals from rapidly evolving into pathological gambling.